The Potential Association of Later Initiation of Oral/Enteral Nutrition on Euthyroid Sick Syndrome in Burn Patients - Joaquín Pérez-Guisado; Jesús M. de Haro-Padilla; Luis F. Rioja; Leo C. DeRosier; Jorge I. de la Torre (International Journal of Endocrinology)
Objective. The aim of this study was to determine if early initiation of oral/enteral nutrition in burn patients minimizes the drop in fT3 levels, reduces the potential for euthyroid sick syndrome (ESS), and shortens the length of hospital stay (LHS). Subjects and Methods. We retrospectively evaluated the statistical association of serum fT3, fT4, and TSH at the first (2nd–5th day) and second sample collection (9th–12th day) after the burn injury in 152 burn patients. Three groups were established depending on time of initiation of the oral/enteral nutrition: <24 h before the injury (Group 1), 24–48 h after the injury (Group 2), and >48 h after the injury (Group 3). Results. They were expressed as mean ± standard deviation. We found that LHS and the fT3 levels were statistically different in the 3 groups. The LHS (in days) was, respectively, in each group, 16.77±4.56, 21.98±4.86, and 26.06±5.47. Despite the quantifiable drop in fT3, ESS was present only at the first sample collection (2.61±0.92 days) in Group 3, but there was no group with ESS at the second sample collection (9.89±1.01 days). Our data suggest that early initiation of nutritional supplementation decreases the length of hospitalization and is associated with decreasing fT3 serum concentration depression. Conclusion. Early initiation of oral/enteral nutrition counteracts ESS and improves the LHS in burn patients.